2011
DOI: 10.1111/j.1526-100x.2011.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Preferential Associates to Initiate Restoration Plantings

Abstract: Ecological restoration typically aims to re-establish dominant plant species and their native associates, despite the lack of guidance on which associates to introduce initially. Analysis of naturally occurring plant communities can provide criteria to shorten the list of species that are associated with dominants, in order to focus revegetation efforts on species likely to establish. Using the example of sedge meadows, we evaluated wetland vegetation data from Laurentian Great Lakes wetlands to identify "pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…The constructed wetland accumulated 0.4 g P m -2 year -1 . A similar accumulation of phosphorus was shown by Johnston [4], whereas a study by Wang et al [24] into the accumulation of phosphorus in deposits supplied with sewage showed phosphorus to accumulate at a rate of 30 g P m -2 year -1 .…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The constructed wetland accumulated 0.4 g P m -2 year -1 . A similar accumulation of phosphorus was shown by Johnston [4], whereas a study by Wang et al [24] into the accumulation of phosphorus in deposits supplied with sewage showed phosphorus to accumulate at a rate of 30 g P m -2 year -1 .…”
Section: Resultssupporting
confidence: 73%
“…This greatly reduces the effects of the sewage treatment plant construction program in rural areas. In order to improve sewage management and to protect waters from a harmful excess of biogenic elements, the various methods employed should include the natural biological, physical and chemical processes that take place in natural and constructed wetlands, which very effectively stimulate biological treatment of water [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…were typically found at the base of cattail stems or growing out from the house, while the wetland obligate, Bidens spp., was also largely found growing on cattail mats (Z. X. Kua, personal communication ). Among the species identified to occur more in muskrat‐disturbed transects, three taxa (i.e., Lysimachia spp., Scutellaria spp., and Cicuta bulbifera ) were plants associated with sedge tussock mounds (Johnston and Zedler 2012). In this case, muskrat house structures may create similar physical structures which allow these tussock‐associated plants to occur more frequently around muskrat houses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the higher abundance of Lemna minor around muskrat‐disturbed areas may be associated with the habitat type associated with muskrat activity. The lesser presence of C. lacustris around muskrat houses, alongside P. arundinacea, was also identified as wetland plants associated with tussock mounds (Johnston and Zedler 2012). However, inferences made based on these observed differences remain speculative and will require further studies and observations to help properly understand these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Carex stricta supports biodiversity, including several associates recommended for introduction after the C. stricta matrix is well established in restoration sites (Johnston and Zedler 2012). Tussocks add surface area (40% more with 15-25 cm-tall tussocks; Werner and Zedler 2002), provide topographic heterogeneity, and grow early in spring, allowing temporal segregation (Peach and Zedler 2006;this study).…”
Section: Wetland Monitoringmentioning
confidence: 99%